Efficacy of two intraoral scanners: perception of postgraduate students of a private university in Lima - Flores-Mas, Ricardo (2024)
Objective: To determine the perception of postgraduate students of a private university in Lima on the efficacy of the intraoral scanners (IOS) Primescan Dentsply Sirona® and Virtuo Vivo Straumann®. Materials and methods: Cross-sectional study in which 10 students of Oral Rehabilitation participated, who, after being trained, scanned a model using both IOS; subsequently, their perceptions were collected through a questionnaire. Results: The Primescan Denstply Sirona® IOS was considered by 80% (n = 8) and 100% (n = 10) of the students as having the best characteristics in scanning speed and flow, respectively; and the Straumann® Virtuo Vivo IOS was considered the most ergonomic by 100% (n = 10). Conclusions: The IOS Primescan Denstply Sirona® IOS was perceived as the fastest, sharpest and with the best scanning flow; and the Straumann® Virtuo Vivo IOS was considered the most ergonomic and preferred.